THE ROLE OF PR-COMMUNICATIONS IN FORMING A POSITIVE IMAGE OF UNIVERSITY STUDENT SPORT TEAMS (ON THE EXAMPLE OF FC «SUMDU») - Yaremenko, Vadym (Global Prosperity, 2021)
The article defines the role of PR communications in shaping the positive image of the national university student sports team. During the research, attention was focused on a specific object - the football club of Sumy State University, «SumDU.» As a result, the features of PR-communications implemented by this team were revealed: providing well-known Internet media of Sumy region and Ukraine with positive facts from its sports live and forming feedback mechanisms with the audience on these resources in order to obtain an opinion on such information and, if necessary, to correct and supplement it; to introduce the communication methods that realize the unique image goals of the university; to translate the values that interest financially stronger organizations to carry out effective sponsorship activities; to support the social PR-projects of famous athlete-students. It is also noted that as a result of implementing the identified features of PR communications, a number of positive image characteristics of the university sports teams are formed. It is presented as a center in the training of highly competitive professional athletes of Sumy region; facility for providing attractive information about the sports life of the same region; a platform for implementing a powerful educational and professional campaign of the university and unique PR-projects of its «star» athlete; a project for profitable sponsorship by organizations with high financial status, which allows increasing its competitive and financial level. It was found that the presentation of this image content in PR-communications is the result of the correct using the resource potential of the university sports teams. The results of this article are of practical value for developing the positive image strategies of modern universities sports teams and have become an important fact that will further develop this scientific area.